Labor market conditions and self-employment: A Denmark-Spain comparison - Raquel Carrasco; Mette Ejrnæs (IZA Journal of Labor Policy, 2012)
Among the OECD countries, Spain faces one of the highest rates of self-employment and Denmark one of the lowest, being the difference specially relevant among women. These two countries present important differences in their labor market conditions in terms of labor market flexibility, generosity of the unemployment benefits system, child care policies, and barriers to start and operate a business. In this paper we analyze if the different institutional environment and employment conditions in both countries can help to interpret the different incidence of self-employment rates. The study is carried out for men and women separately using a strictly comparable panel data set. The results indicate that in Spain self-employment seems to offer individuals who normally are considered as marginalized in the labor market a beneficial alternative to wage employment, while this pattern is not so clear in Denmark. Specifically, in Spain those individuals in the bottom part of the wage distribution and non-employees, particularly unemployed without unemployment benefits and mothers with small children, start more often their own business than in Denmark.
Keywords: E64; J18; J38; J58; J24; J44; J62; 330; self-employment; labor transitions; employment conditions; Selbstständige; Arbeitsmarkt; Systemvergleich; Spanien; Dänemark